Effects ofS-nitroso-N-acetylcysteine on contractile function of reperfused skeletal muscle - Nasser, Rima M. (1998)
The ultimate goal of replantation and microsurgical reconstructive operations is to regain or improve impaired function of the tissue. However, the data related to the influence of NO on tissue function are limited. This study evaluated the effects of the NO donorS-nitroso-N-acetylcysteine (SNAC) on contractile function of skeletal muscle during reperfusion. Forty-nine rats were divided into six groups. The extensor digitorum longus (EDL) muscles in groups I andII were not subjected to ischemia-reperfusion but were treated with a low (100 nmol/min) or high (1 μmol/min) dose of SNAC. Ingroups III-V, the EDL underwent 3 h of ischemia and 3 h of reperfusion and was also treated with low (100 nmol/min) or high doses (1 or 5 μmol/min) of SNAC. Group VI was a phosphate-buffered saline (PBS)-treated control group. Twenty additional animals were used to document systemic effects of SNAC and PBS only. SNAC or PBS was infused for 6.5 h, beginning 30 min before ischemia and continuing throughout the duration of reperfusion. Contractile testing compared the maximal twitch force, isometric tetanic contractile forces, fatigue, and fatigue half time of the experimental EDL and the contralateral nontreated EDL. The findings indicate that1) SNAC does not influence contractile function of EDL muscle not subjected to ischemia-reperfusion, 2) SNAC significantly protects the contractile function of ischemic skeletal muscle against reperfusion injury in the early reperfusion period, and 3) the protective role of SNAC is critically dosage dependent; protection is lost at higher doses. The conclusion from this study is that supplementation with exogenous NO exerts a protective effect on the tissue against reperfusion injury. it is now well accepted that NO, a signaling molecule, is involved in many important physiological and pathological functions, including vessel relaxation, neurotransmission, and pathogen suppression (5). NO is synthesized froml-arginine by NO synthase (NOS). Three major NOS isoforms exist. NOS 1 is a constitutive isoform found in the central and peripheral nervous systems, epithelial cells, and skeletal muscle (11). Neurotransmission, bronchodilation, glucose transport, and regulation of force development are among its functions. NOS 2 (iNOS) is induced by endotoxins and cytokines in most cells (20). This enzyme is believed to release larger amounts of NOx (nitrogen oxides), which may be important in host defense (20). NOS 3 is a Ca2+-calmodulin-dependent constitutive isoform found in vascular endothelial cells, some neuronal populations, platelets, cardiac muscle, and skeletal muscle. Its major activities include relaxation of vascular smooth muscle, inhibition of platelet activation and adhesion, and control of cell respiration (16,24). Although many studies have examined the role of NO in ischemia-reperfusion injury of cerebral, myocardial, mesenteric, gastric, and lung tissues (2, 17, 19), the results are paradoxical and no consensus has been reached. In skeletal muscle, the one existing report suggested that NO production during reperfusion injury may be deleterious to survival of muscle tissue (26). However, it has become apparent that the success of replantation and microsurgical reconstructive operations should not be measured by survival alone but also by quantification of subsequent function. The ultimate goal is to regain normal function or, at least, to improve impaired function. To our knowledge, there are no data in the literature pertaining to functional regulation by NO in the reperfused skeletal muscle. The present study was designed to test the hypothesis that NO influences the contractile function of reperfused skeletal muscle.